2023
DOI: 10.3390/ijms24108525
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution of Humoral and T-Cell Specific Immune Response to COVID-19 mRNA Vaccine in Patients with Multiple Sclerosis Followed until the Booster Dose

Abstract: This study characterizes antibody and T-cell immune responses over time until the booster dose of COronaVIrus Disease 2019 (COVID-19) vaccines in patients with multiple sclerosis (PwMS) undergoing different disease-modifying treatments (DMTs). We prospectively enrolled 134 PwMS and 99 health care workers (HCWs) having completed the two-dose schedule of a COVID-19 mRNA vaccine within the last 2–4 weeks (T0) and followed them 24 weeks after the first dose (T1) and 4–6 weeks after the booster (T2). PwMS presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…This is consistent with studies in the healthy population, where cellular immunity to COVID‐19 vaccination and infection tends to be more durable than antibody responses 46 . Robust longitudinal cellular immunity in B‐cell‐depleted MS patients is a consistent finding across multiple studies 28,36,47–50 . Booster further raised cytokine responses four to fivefold.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is consistent with studies in the healthy population, where cellular immunity to COVID‐19 vaccination and infection tends to be more durable than antibody responses 46 . Robust longitudinal cellular immunity in B‐cell‐depleted MS patients is a consistent finding across multiple studies 28,36,47–50 . Booster further raised cytokine responses four to fivefold.…”
Section: Discussionsupporting
confidence: 84%
“…46 Robust longitudinal cellular immunity in B‐cell‐depleted MS patients is a consistent finding across multiple studies. 28 , 36 , 47 , 48 , 49 , 50 Booster further raised cytokine responses four to fivefold. This was a similar‐fold increase as after the primary vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to multiple factors, including reduced T-cell–specific or humoral-specific responses, which leads to low seroconversion rates post-vaccination, generation of antibodies with low neutralization activity against SARS-CoV-2 ( 41 43 ), and a short duration of protection. Studies have shown that although alterations in the B-cell compartment correlate with decreased humoral responses to COVID-19 vaccines, some degree of T-cell–mediated protection from severe disease might be conserved ( 23 , 44 , 45 ). A meta-analysis of 82 studies ( 46 ) showed that after one vaccine dose, people with hematological cancers, immune-mediated inflammatory disorders, and solid cancers were half less likely to seroconvert, while transplant recipients were 16 times less likely to seroconvert (risk ratio 0.06 [95% CI 0.04–0.09]) compared with immunocompetent controls.…”
Section: Gaps In the Current Management Landscape For Immunocompromis...mentioning
confidence: 99%
“…Ruggieri’s article focuses on characterizing the immune responses, including antibodies and T-cells, in patients with multiple sclerosis (PwMS) who are receiving various disease-modifying treatments (DMTs) after receiving COVID-19 vaccines [ 44 ]. A total of 134 PwMS and 99 healthcare workers (HCWs) who had completed the two-dose COVID-19 mRNA vaccine schedule within the last 2–4 weeks (T0) were prospectively enrolled.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%